1999
DOI: 10.1046/j.1365-8711.1999.02413.x
|View full text |Cite
|
Sign up to set email alerts
|

On the magnetic acceleration and collimation of astrophysical outflows

Abstract: The axisymmetric 3-D MHD outflow of a cold plasma from a magnetized and rotating astrophysical object is numerically simulated with the purpose of investigating the outflow's magnetocentrifugal acceleration and eventual collimation. Gravity and thermal pressure are neglected while a split-monopole is used to describe the initial magnetic field configuration. It is found that the stationary final state depends critically on a single parameter alpha expressing the ratio of the corotating speed at the Alfven dist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
121
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 106 publications
(130 citation statements)
references
References 35 publications
(48 reference statements)
9
121
0
Order By: Relevance
“…The phenomenon does not appear to have been much considered in the astrophysical context in contrast to magnetic collimation or magnetic centrifugal acceleration (e.g. Bogovalov & Tsinganos 1999;Banerjee & Pudritz 2006). The most simple r θ manner to appreciate the phenomenon is through the magnetic pressure, B 2 /2μ 0 (Demichev et al 1965).…”
Section: Magnetic Deflection Of the Ejecta In The Omc-1 Explosionmentioning
confidence: 99%
“…The phenomenon does not appear to have been much considered in the astrophysical context in contrast to magnetic collimation or magnetic centrifugal acceleration (e.g. Bogovalov & Tsinganos 1999;Banerjee & Pudritz 2006). The most simple r θ manner to appreciate the phenomenon is through the magnetic pressure, B 2 /2μ 0 (Demichev et al 1965).…”
Section: Magnetic Deflection Of the Ejecta In The Omc-1 Explosionmentioning
confidence: 99%
“…In the special relativistic domain, simulations have been presented for coronal winds (Bogovalov & Tsinganos 1999;Tsinganos & Bogovalov 2002), and in the general relativistic domain for disk winds (e.g. Koide et al 1999Koide et al , 2001 to model the formation and collimation of relativistic outflows in the vicinity of black holes.…”
Section: Introductionmentioning
confidence: 99%
“…In Bogovalov & Tsinganos (1999) and Tsinganos & Bogovalov (2000) it was found that, for a uniformly rotating base, only a small part of the total massand magnetic flux is collimated cylindrically. This fraction is only about 1% of the corresponding values of an assumed uncollimated outflow, i.e.…”
Section: Introductionmentioning
confidence: 96%